The transcultural adaptation and validation of the Chinese version of the Attitudes Toward Recognizing Early and Noticeable Deterioration scale - Li, Wenbo; Yu, Hongyu; Li, Bing; Zhang, Yanli; Fu, Mingshu (Frontiers in Psychology, 2022)
Background: In China, clinical deterioration events present a real problem for every clinical nurse. Patient deterioration is determined in part by nurses' attitudes toward early recognition of clinical deterioration. However, research on attitudes toward early identification of clinical deterioration is still in its infancy, and even less research has been done on ward nurses' attitudes toward early identification of clinical deterioration. To drive behavioral change and improve the care of deteriorating patients, nurses need comprehensive, valid, and reliable tools to assess their attitudes toward early identification of deterioration.Objective: In this study, the Attitudes Toward Recognizing Early and Noticeable Deterioration (ATREND) scale will be translated into Chinese, and its validity and reliability tests will be assessed among ward nurses.Methods: From March 2022 to July 2022, ATREND was translated, back-translated, and cross-culturally adapted into the Chinese version using a modified Brislin translation model, and then 460 ward nurses were recruited in total from tertiary Grade A general hospitals in two cities- Shenyang and Jinzhou in Liaoning Province, China. Reliability analyses were conducted by internal consistency reliability, split-half reliability, and test-retest reliability. We convened a committee of experts to determine the validity of the content. Tests of the structural validity of the scale were conducted using exploratory and validation factor analyses. Results: The Cronbach’s α value of the Chinese version of ATREND was 0.804, and the Cronbach’s α value of the dimensions ranged from 0.782 to 0.863. The split-half reliability and test-retest reliability were 0.846 and 0.711, respectively. Furthermore, the scale has an index of content validity of 0.922, which is a high level of content validity. The three-factor model supported by this study was confirmed by confirmatory factor analysis. In exploratory factor analysis, eigenvalues, total variance explained, and scree plot supported a three-factor structure. Moreover, the model fitting indexes were all within acceptable limits based on the confirmatory factor analysis.Conclusion: Among ward nurses, the Chinese version of the ATREND is reliable and valid. As a result, it is necessary to consider the Chinese scale's three-factor structure.